Eight new species of Australian stiletto flies in the genus Anabarhynchus Macquart (Diptera: Therevidae) from South East Queensland - Ferguson, David J.; Lambkin, Christine L.; Yeates, David K. (Zootaxa, 2014)
We describe, diagnose and illustrate eight new species in the genus Anabarhynchus Macquart, 1848 as follows: Anabarhynchus cretatus sp. n., Anabarhynchus darembal sp. n., Anabarhynchus iancommoni sp. n., Anabarhynchus longiseta sp. n. Anabarhynchus lyncurium sp. n., Anabarhynchus moretonensis sp. n., Anabarhynchus neboensis sp. n. and Anabarhynchus wintertoni sp. n. These represent all new species in collections from south east Queensland. These new species bring the total number of described Australian species in the genus to 112.